Complement activation in hidradenitis suppurativa: a new pathway of pathogenesis?. (1st August 2018) - Kanni, T.; Zenker, O.; Habel, M.; Riedemann, N.; Giamarellos‐Bourboulis, E.J.
Summary: Background: Despite the heavy purulence observed in hidradenitis suppurativa (HS), the kinetics of complement anaphylatoxins acting to prime chemotaxis of neutrophils has not been studied. Objectives: To explore complement activation in HS. Methods: Circulating concentrations of complement factor C5a, as well as of membrane attack complex C5b‐9, were determined in the plasma of 54 treatment‐naïve patients and of 14 healthy controls, as well as in the pus of seven patients. Results were correlated with Hurley stage and International Hidradenitis Suppurativa Severity Score. Peripheral blood mononuclear cells (PBMCs) were isolated from seven patients with Hurley stage III HS and seven healthy volunteers and stimulated in the presence of 25% of plasma for the production of tumour necrosis factor‐α (TNF‐α). Results: Circulating C5a and C5b‐9 were significantly greater in patient than in control plasma; however, concentrations in pus were very low. Circulating C5a levels exceeding 28 ng mL −1 were associated with a specificity > 90% with the occurrence of HS. Circulating levels of C5a and C5b‐9 were greater in patients with more severe HS. PBMCs of patients produced high concentrations of TNF‐α only when growth medium was enriched with patient plasma; this was reversed with the addition of the C5a blocker IFX‐1. Conclusions: Systemic complement activation occurs in HS and may be used as a surrogate biomarker of HS. C5a stimulates overproduction of TNF‐α and may be a future therapeutic target.